Pilihan Bahasa pada Komunitas Tutur Pasar Baruga - Laode Abdul Wahab (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2015)
AbstractThe language choice in the Speech Community of Baruga market is an interesting phenomenon. The object of research is the speeches. Data was collected from 70 locus using listening methods both in recording technique and writing technique. Results of the data analysis found that the choice of language in the Speech Community of Baruga market patterned by the useof language in the social interaction. Pattern choice in this speechcommunity appears in the relationship between background, the role of the relationship between the participants, and subject of speech. Language variation as repertoire in the Speech Community of Baruga market include (1) a single variation of language, which includes a) a variation of Indonesian language; b) Javanese language; c) Tolakinese language; d) Bugisnese language; e) Makassarnese language; f) Sundanese language; g)Munanese language; h) Wawoniinese language; i) Erekenese language; j) Ambonese language; k) Wakatobinese language, and 2) variations in the code switching, and 3) variations in the code-mixing. The Speech Community of Baruga market also form diglossia communities and experiencing double overlapping diglossia or different situation degree and language functions which are multiple and double-nested diglossia or the situation in multilanguage societies. There are two languages differentiatedas the high languages in one side and the low languages in other side. Keywords: Language Choice, Speech Community of Baruga market AbstrakPilihan bahasa dalam komunitas tutur Pasar Baruga merupakan fenomena menarik. Objek penelitian adalah tuturan. Data dikumpulkan dari 70 lokus menggunakan metode simak, melalui teknik rekam dan teknik catat. Hasil analisis data menghasilkan temuan bahwa pilihan bahasa dalam komunitas tutur Pasar Baruga terpola berdasarkan ranah pemakaian bahasa dalaminteraksi sosial. Pola pilihan dalam komunitas tutur ini tampak pada hubungan antara latar, hubungan peran antar-peserta tutur, dan pokok pembicaraan. Variasi bahasa sebagai khazanah (repertoar) bahasa komunitas tutur Pasar Baruga mencakup (1) Variasi tunggal bahasa, yang meliputi a) variasi bahasa Indonesia; b) variasi bahasa Jawa (BJ); c) variasi bahasa Tolaki (BT); d) variasi bahasa Bugis (BG); e) variasi bahasa Makassar (BM); f) variasi bahasa Sunda (BS); g) variasi bahasa Muna (BMU); h) variasi bahasa Wawonii (BWW); i) variasi bahasa Ereke (BE); j) variasi bahasa Ambon (BA); k) variasi bahasa Wakatobi (BWK), dan 2) variasi alih kode, dan 3) variasi campur kode. Komunitas tutur Pasar Baruga juga membentuk komunitas yang diglosik dan mengalami double overlapping diglosia atau situasi pembedaan derajat dan fungsi bahasa secara berganda dan double-nested diglosia atau keadaan dalam masyarakat multilingual. Terdapat dua bahasa yang diperbedakan satu sebagai bahasa tinggi, danyang lain sebagai bahasa rendah. Kata Kunci: Pilihan Bahasa, Komunitas Tutur Pasar Baruga